PgpP is a broadly conserved phosphatase required for phosphatidylglycerol lipid synthesis - Angelika Gründling; Anna P. Brogan; Michael J. James; Fernando H. Ramirez-Guadiana; Ian J. Roney; Thomas G. Bernhardt; David Z. Rudner (Proceedings of the National Academy of Sciences, 2025)
The cytoplasmic membrane of bacteria is composed of a phospholipid bilayer made up of a diverse set of lipids. Phosphatidylglycerol (PG) is one of the principal constituents and its production is essential for growth in many bacteria. All the enzymes required for PG biogenesis in Escherichia coli have been identified and characterized decades ago. However, it has remained poorly understood how gram-positive bacteria perform the terminal step in the pathway that produces this essential lipid. In E. coli, this reaction is mediated by three functionally redundant phosphatases that convert phosphatidylglycerophosphate (PGP) into PG. Here, we show that homologs of these enzymes in Bacillus subtilis are not required for PG synthesis. Instead, we identified a previously uncharacterized B. subtilis protein, YqeG (renamed PgpP), as an essential enzyme required for the conversion of PGP into PG. Expression of B. subtilis or Staphylococcus aureus PgpP in E. coli lacking all three Pgp enzymes supported the growth of the strain. Furthermore, depletion of PgpP in B. subtilis led to growth arrest, reduced membrane lipid staining, and accumulation of PGP. PgpP is broadly conserved among Firmicutes and Cyanobacteria. Homologs are also present in yeast mitochondria and plant chloroplasts, suggesting that this widely distributed enzyme has an ancient origin. Finally, evidence suggests that PgpP homologs are essential in many gram-positive pathogens and thus the enzyme represents an attractive target for antibiotic development.